The Portuguese Sustainable Campus Network: a knowledge collaboration for sustainability transformation in higher education institutions - Barros, Manuel (2023)
Networks are an important mechanism for systemic change toward sustainability in higher education institutions. In Portugal, there is no formal law or regulation at the governmental level pressuring for this change. Also, there was a need for action and a lack of collaboration between the Portuguese higher education community to allow an advanced sustainability implementation in higher education institutions. This chapter presents the activities that the Portuguese Network Sustainable Campus—Rede Campus Sustentável (RCS) has been undertaking. The history and organization of the network are presented as well as a summary of its main initiatives, namely the results of the first survey report on the Implementation of Sustainability in Higher Education in Portugal, where the actual practices in the main dimensions are listed. This work aims to contribute to the studies about sustainability-oriented networks in higher education, addressing its current and future challenges.